Prevalence of deep and ovarian endometriosis in women attending a general gynecology clinic: prospective cohort study. (17th April 2023) - Chaggar, P.; Tellum, T.; Thanatsis, N.; De Braud, L. V.; Setty, T.; Jurkovic, D.
ABSTRACT: Objectives: To assess using transvaginal ultrasound the prevalence of deep and ovarian endometriosis in premenopausal women attending a general gynecology clinic. We also investigated whether the presence of endometriosis was associated with various demographic factors and other pelvic abnormalities. Methods: This was a prospective observational cohort study carried out between February 2019 and October 2020. Consecutive premenopausal women who attended our general gynecology clinic underwent pelvic ultrasound examination, performed by a single experienced operator. Pregnant women and those with a history of hysterectomy or oophorectomy were excluded. The primary outcome was the prevalence of deep and/or ovarian endometriosis. Secondary outcomes were the anatomical distribution of endometriotic lesions and the association of endometriosis with demographic characteristics and various pelvic abnormalities, which were analyzed using logistic regression and multivariable analysis. Results: A total of 1026 women were included in the final study sample, of whom 194 (18.9% (95% CI, 16.6–21.4%)) had sonographic evidence of deep and/or ovarian endometriosis. Of the 194 women diagnosed with endometriosis, 106 (54.6% (95% CI, 47.4–61.8%)) were diagnosed with endometriotic nodules only, 26 (13.4% (95% CI, 9.0–19.0%)) with ovarian endometriomas only, and 62 (32.0% (95% CI, 25.5–39.0%)) women had evidence of both. There was a total of 348 endometriotic nodules in 168 women, located most frequently in the retrocervical area (166/348; 47.7% (95% CI, 42.4–53.1%)), uterosacral ligaments (96/348; 27.6% (95% CI, 23.0–32.6%)) and bowel (40/348; 11.5% (95% CI, 8.3–15.3%)). Multivariable analysis found significant positive associations between endometriosis and both adenomyosis (odds ratio (OR), 1.72 (95% CI, 1.10–2.69); P = 0.02) and pelvic adhesions (OR, 25.7 (95% CI, 16.7–39.3); P < 0.001), whilst higher parity (OR, 0.44 (95% CI, 0.24–0.81); P = 0.03) and history of Cesarean section (OR, 0.18 (95% CI, 0.06–0.52); P = 0.002) were associated with a lower occurrence of endometriosis. A total of 75/1026 women (7.3% (95% CI, 5.8–9.1%)) underwent laparoscopy within 6 months of pelvic ultrasound examination. There was very good agreement between ultrasound and surgical findings, with a kappa value of 0.84 (95% CI, 0.69–0.99). Conclusions: Deep and/or ovarian endometriosis was present in nearly one in five women attending a general gynecology clinic. There were significant positive associations with adenomyosis and pelvic adhesions and negative associations with higher parity and previous Cesarean section. © 2023 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.